INSEMINACIÓN INTRAUTERINA VÍALAPAROSCÓPICA DE OVEJAS BLACK BELLY CON SEMEN CONGELADO - Mellisho S., Edwin (2013)
The present studywas carried out to evaluate the pregnancy rate of Black Belly ewes reared under the conditions of the Peruvian coast, that were laparoscopic intrauterine inseminated with frozen-thawed pellet semen. Females were divided according to age and reproductive historyin nulliparous (n = 21) and ewes (n = 17). Estrous synchronization was done using vaginal sponges (60 mg medroxyprogesterone acetate) for 13 days and the injection of 300 IU equine chorionic gonadotrophin upon sponge removal. The intrauterine insemination was conducted at fixed time (62-65 h post withdrawal of vaginal sponge) using a semen dose (0.4 ml, 40 x 106 spermatozoa) into the lumen of each uterine horn. Sedatives or tranquilizers were not used. Ultrasound pregnancy diagnosis was performed at day 35 after insemination.No significant differenceswere found in pregnancy rates between nulliparous (71.4%) and ewes (64.7%). The high pregnancy rates when using laparoscopic intrauterine insemination with frozen-thawed semen in Black Belly females supports the use of this technique for breeding elite animals.